Optical chemical sensors using polythiophene derivatives as active layer for detection of volatile organic compounds - Goncalves, V. C. [UNESP]; Balogh, D. T. (Elsevier B.V. Sa, 2012)
Several studies on polythiophene gas sensors, based mainly on electrochemical and gravimetric principles can be found in the literature. However, other principles of gas detection, such as optical and thermal, are still little studied. Optical sensing is suitable for remote detection and offers great versatility at low cost. Here,we report on the use of thin films of seven polythiophene derivatives as active layer in optical sensors for the detection of six volatile organic compounds (n-hexane, toluene, tetrahydrofuran, chloroform, dichloromethane and methanol) and water vapor, in concentration range of 500-30,000 ppm. The results showed that it is possible to use different polythiophene derivatives to differentiate VOCs by optical sensing. Differentiation can be performed based on the presence or not of response to an analyte and the sensitivity value of the sensors for the analytes. Another important feature is the lack of the effect of humidity on the response of most films, which could be a major drawback in the application of these sensors. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Optical sensor; Gas sensor; Conjugated polymer; Polythiophene